Success of Decade-Old Business in Northern Philippines - Keith Edorhia Gannaban; Angelica Gasque; Giechelle Kette Libunao; Karen Joy Catacutan; Jonighna Mei Alagao (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to determine what internal and external factors affect the success of a decade-old business in Tuguegarao City, Northern Philippines. A quantitative research design employing descriptive research method was used in the study. A structured questionnaire that included business profiles and internal and external factors affecting business success was used in collecting data from 100-decade-old business owners in Tuguegarao City. Results showed that the most important factor affecting the success of decade-old businesses are the internal factors, while external factors are considered necessary for business success. Customer service, communication, and analytical skills are the most important under internal factors, while family advice is the most important under external factors.